Adoption of flood preparedness actions: A household level study in rural communities in Tabasco, Mexico. (September 2017) - Atreya, Ajita; Czajkowski, Jeffrey; Botzen, Wouter; Bustamante, Gabriela; Campbell, Karen; Collier, Ben; Ianni, Francisco; Kunreuther, Howard; Michel-Kerjan, Erwann; Montgomery, Marilyn
Abstract: Of all the natural disasters, floods are the most common. While they affect most countries around the world, poor communities are particularly vulnerable to flood risk. The use of early preparedness measures is key for minimizing related flood impacts; however, little is known about what drives their adoption by households in those communities. We undertake a household survey of individual flood preparedness decisions in ten communities in the Mexican state of Tabasco, which are exposed to frequent flooding and also highly vulnerable from a socio-economic perspective. Statistical analysis reveals that in these communities having accessible flood risk maps, sharing flood experiences with family, having early warning systems, and having shelters, amongst other factors, all increase the likelihood of household preparedness actions. This information is important as it can be used to assist in diagnosing the existing capacities and gaps in managing flood risk in these communities. For example, while having knowledge of the risk map is found to significantly increase the likelihood of protecting the belongings, only 8% of the survey respondents were aware of their community's risk map.